Efficient and Secure Cloud Log Secrecy Scheme for Cloud Forensics - M, Vijeth; HR, Vikas; N, Vishwas; Kumar, Prasanna M, Vishwas B (International Journal of Computer Sciences and Engineering, 2025)
Client action logs can be a profitable wellspring of data in cloud legal examinations .thus, guaranteeing the unwavering quality and security of such logs is significant. Most existing proposition for secure logging is intended for conventional environment as opposed to the perplexing condition of the cloud. The log documents present in the log records ought to be protected from aggressors and outsider associations. Log Files contains private data about the association's action. So as to conquer the assaults from outside elements, In this paper, we propose the Efficient and secure log secrecy schemefor cloud forensics process as an elective plan for the verifying of logs in a cloud domain. In Efficient and secure log secrecy scheme for cloud forensics, logs are encrypted utilizing the individual client's public key with the goal that just the client can decrypt the substance. So as to avert unapproved change of the log, we produce proof of past log (PPL) using cryptography techniques.